2020
DOI: 10.1007/s00405-020-06131-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl alcohol threshold test: a fast, reliable and affordable olfactory Assessment tool for COVID-19 patients

Abstract: Objective COVID-19 patients may present mild symptoms. The identification of paucisymptomatic patients is paramount in order to interrupt the transmission chain of the virus. Olfactory loss could be one of those early symptoms which might help in the diagnosis of COVID-19 patients. In this study, we aim to develop and validate a fast, inexpensive, reliable and easy-to-perform olfactory test for the screening of suspected COVID-19 patients. Study design Phase I was a case-control study and Phase II a transversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 30 publications
0
31
0
6
Order By: Relevance
“…Of the patients, 84.8 per cent had at least one chemosensitive disorder at baseline; this frequency is higher than that reported in some other psychophysical studies which evaluated patients at later stages of the disease. [12][13][14][15][16][17] At the end of the observation period, patients presented with mild hyposmia or hypogeusia in 15.2 per cent and 3.6 per cent of cases, respectively. These frequencies are in line with those normally We concur with the findings of Moein et al, 15 which suggest that self-reported olfactory or gustatory loss underestimates the frequency of chemosensitive disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the patients, 84.8 per cent had at least one chemosensitive disorder at baseline; this frequency is higher than that reported in some other psychophysical studies which evaluated patients at later stages of the disease. [12][13][14][15][16][17] At the end of the observation period, patients presented with mild hyposmia or hypogeusia in 15.2 per cent and 3.6 per cent of cases, respectively. These frequencies are in line with those normally We concur with the findings of Moein et al, 15 which suggest that self-reported olfactory or gustatory loss underestimates the frequency of chemosensitive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Objective psychophysical evaluation is challenging because of logistical and safety problems. Consequently, as of 1 July 2020, only six retrospective psychophysical studies have been published, [12][13][14][15][16][17] and only three of them investigate both olfactory and gustatory functions. [12][13][14] In the absence of prospective studies, the long-term recovery rate of chemosensitive function has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…As such, some of our study's subjects described decreased strengths of household odorants suggestive of lower threshold scores, while still accurately identifying BSIT odorants at close proximity. On the other hand, alcohol threshold testing has detected olfactory dysfunction in self‐reported normosmic COVID‐19 hospitalized patients 30 . Therefore, future investigations utilizing psychophysical tests that query threshold, discrimination, and identification (TDI) of odorants may better characterize objective olfactory dysfunction and potentially result in a stronger correlation between self‐reported and measured olfactory scores 31 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Hyposmia, with or without hypogeusia, has been suggested as a potentially reliable indicator of mild COVID-19 and is being used in screening for COVID-19. 4,5 On the contrary however, it has been considered that olfactory and gustatory dysfunctions are self-limiting in the great majority of COVID-19 patients. 6 However, there are rare reports investigating the prognosis of olfactory and gustatory dysfunctions in .…”
Section: Introductionmentioning
confidence: 99%